Moral Hukum Pembatasan Akses Pekerjaan Bagi Mantan Narapidana dalam Bidang Notaris - Irbad Aldo Sari; Irwan Santosa; Mohammad Ryan Bakry (Jurnal Pendidikan Indonesia, 2025)
Legal protection for a former convict is very much needed to obtain a job and a decent livelihood.Penelitian ini dengan rumusan masalah bagaimanakah konsep hak atas akses pekerjaan bagi mantan narapidana di Indonesia dan Bagaimanakah moral hukum pembatasan akses pekerjaan dalam bidang notaris.The purpose of this research is to analyze and examine the protection of the rights of former convicts and to analyze societal stigma towards the lives of former convicts regarding access to employment in the notary field. Jenis penelitian ini adalah penelitian yuridis normatif. The focus of this research is to analyze the protection of the rights of former convicts and the societal stigma towards the lives of former convicts regarding access to jobs in the notary field. Hasil penelitian ini Because a prisoner who has served a sentence means he has atoned for his crime by sacrificing his freedom for a certain period for the crime he committed. If the person has been released, then they have completed serving their sentence, and when they return to society, they should not The existence of Article 3 letter (h) of the UUJN-P actually protects the human rights of prospective notaries who have a good track record. Sehingga dengan adanya pasal 3 huruf (h) UUJN-P ini juga sebagai filter untuk menyaring orang-orang yang berkompeten demi mewujudkan sosok notaris yang terhormat, berintegritas dan juga berkredibilitas tinggi. there is an exception for him in obtaining his legal rights.